Земная ось - Брюсов Валерий Яковлевич (Триада-Файн, 1993)
Экземпляры: ф.1 (2004) / Инвентарный номер: 48246 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 89 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)6-44